Accelerating Postpartum Recovery: Oxytocin Massage Training For Village Midwives - Uswatun Chasanah; Tri Kartikawati; Dewi Mayangsari (Swadaya: Jurnal Pengabdian Masyarakat, 2025)
Purpose: This community service activity aims Improving maternal well-being and reducing postpartum morbidity through oxytocin massage. Methodology: The methods used included hands-on training and mentoring by midwives, and regular monitoring and evaluation at the Purwoharjo Pemalang health centre. This program encourages includes training to hone the skills of village midwives in providing midwifery care to pregnant, delivery, and postpartum women with the specific skill of oxytocin massage to increase the well-being of mothers and babies. Findings: Village midwives in Comal Subdistrict, Pemalang Regency, the working area of Puskesmas Purwoharjo Pemalang, have acquired special skills in providing midwifery care using oxytocin massage.